KARAKTERISTIK MORFOLOGI ARCUS PALATOGLOSSUS DAN ARCUS PALATOPHARYNGEUS TERHADAP SKOR KUESIONER BERLIN PADA MAHASISWA FK USU ANGKATAN 2016 - Vani Wulan Dari (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2021)
Obstructive sleep apnea (OSA) is a major public health problem, with a high prevalence. The Berlin Questionnaire is a questionnaire aimed at OSA screening. Palus palatoglossus and arcus palatopharyngeus are located in the oropharynx which is the most frequent place of OSA. The purpose of this study was to determine the morphological characteristics of the palatoglossus arcus and palatopharyngeus arcus on the Berlin questionnaire on 2016 USU FK students to facilitate OSA screening. This study used a descriptive approach with cross sectional design, while the sampling used primary data, namely in USU FK 2016 students. The palatoglossus arcus and arcatopharyngeus arcus high-risk group classification OSA arcus 1/2 classification (8.8%) . As many as 19.1% of 2016 USU FK students experienced a high risk of OSA. The arcus classification group of 10 respondents at high risk of OSA is arcus 1/2 classification (8.8%). The BMI group of respondents who were at high risk of OSA was obese 1 (8.8%). The neck circumference group of respondents at high risk of OSA is the large neck circumference (14.7%). Based on the nasal congestion group respondents who are at high risk of OSA that is with nasal congestion (17.6%). The palate classification group of respondents at high risk of OSA is the low palate classification (10.3%). From the results of this study it was concluded that respondents with arcus 1/2 classification were the most respondents and also a high risk of OSA.